A late presentation of isolated lymph node tuberculosis postintravesical BCG therapy for superficial bladder cancer: a novel case. (2nd May 2014) - Tasleem, Ali Moostapha; Varga, Branislav; Mahmalji, Wasim; Madaan, Sanjeev
Abstract : Intravesical BCG immunotherapy is commonly used in the treatment of superficial bladder cancer. We recount the case of an 82-year-old British man who completed a course of BCG immunotherapy in 2011 for superficial bladder cancer, and presented in January 2013 with a loss of appetite, loss of weight and severe back pain. CT scanning, followed by MRI displayed a 5.7cm×5 cm conglomerated necrotic, haemorrhagic mass of lymph nodes in the para-aortic region. A CT-guided biopsy revealed granulomatous inflammation, focal fibrosis and acid-fast bacilli consistent with Mycobacterium tuberculosis (TB). The patient was treated with combination antituberculous medication, and is recovering. To our knowledge, this is the only reported case of lymph node TB secondary to intravesical BCG immunotherapy. We suggest that in patients treated with postintravesical BCG with enlarged lymph nodes, a diagnosis of secondary TB should be considered.